Grow in the city, growing the city: urbanisation control in agricultural neighbourhoods of Saint-Louis (Senegal) - (:unkn) unknown (My University, 2018)
This doctoral thesis deals with the modalities of urbanization control in the neighbourhoods of the agricultural belt of the city of Saint-Louis (Senegal). This work is based on the comparison of agri-urban areas with contrasting qualities of development and management. Like other African urban peripheries, these neighbourhoods are facing rapid urbanization unsupervised by the administration. Indeed, they are considered as land reserves and easements of metropolitan facilities by the public authorities. This situation is threatening the quality of the living environment and the cohabitation between agricultural and residential functions. By analysing the interactions between the stakeholders in urban governance, we highlight the key role of local community organisations in taking over the planning, daily management and regulation of uses in these districts.The analysis is structured around two axes. On the one hand, we study power interplays between local organizations, public administrations and international development assistance agencies. We thus report on the concrete interactions between these different stakeholders and their respective strategies through a cross-analysis of four local development and management projects. On the other hand, we analyse the capacity of local associations to mobilise inhabitants to participate in the control of urbanisation in their neighbourhood. We thus show the different stages of maturation of the political process in these areas, through the analysis of the individual and territorial motives and resources of mobilization.
Keywords: African Research